2017
DOI: 10.3346/jkms.2017.32.4.636
|View full text |Cite
|
Sign up to set email alerts
|

Additional Drug Resistance Patterns among Multidrug-Resistant Tuberculosis Patients in Korea: Implications for Regimen Design

Abstract: Detailed information on additional drug resistance patterns of multidrug-resistant tuberculosis (MDR-TB) is essential to build an effective treatment regimen; however, such data are scarce in Korea. We retrospectively analyzed the results of phenotypic drug susceptibility testing (DST) of culture confirmed-TB patients from January 2010 to December 2014 in 7 university hospitals in Korea. MDR-TB was identified among 6.8% (n = 378) of 5,599 isolates. A total of 57.1% (n = 216) of the MDR-TB patients had never be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
16
1
1
Order By: Relevance
“…In European MDR-TB cohorts, on average, only 7.8% were eligible for this shortened regimen [20]. Reports from other areas, including Singapore, Brazil, Pakistan, and South Korea, assume eligibility for the shorter regimen ranged from 30 to 55% [21–24].…”
Section: Discussionmentioning
confidence: 99%
“…In European MDR-TB cohorts, on average, only 7.8% were eligible for this shortened regimen [20]. Reports from other areas, including Singapore, Brazil, Pakistan, and South Korea, assume eligibility for the shorter regimen ranged from 30 to 55% [21–24].…”
Section: Discussionmentioning
confidence: 99%
“…A XDR-TB foi encontrada em 12,4% dos indivíduos. Os altos níveis de resistência encontrados denotam o grande desafio de construir esquemas terapêuticos de sucesso 36 .…”
Section: Pacífico Ocidentalunclassified
“…Additional resistance to pyrazinamide, ofloxacin, and kanamycin was 26.2%–59%, 16.6%–47.5%, and 13.3%–25%, respectively 3 8 9 10 11 . A recent regional survey of drug resistance in South Korea demonstrated that strains from MDR-TB patients had additional resistance to pyrazinamide (35.7%), fluoroquinolones (26.2%), and second-line injectable drugs (19.3%) 53 . Rapid DSTs detecting fluoroquinolone and injectable drug resistance, such as MTBDRsl test, is a prerequisite for identifying patients with MDR-TB eligible for the shorter treatment regimen.…”
Section: Summary Of Major Changes In the 2016 Guidelinesmentioning
confidence: 99%